A review of consent practices and perspectives for pharmacogenetic testing. (September 2016) - Haga, Susanne B; Mills, Rachel
Aim: We aimed to understand consent practices for pharmacogenetic (PGx) testing.Methods: We conducted a literature review and analysis of consent forms from clinical laboratories offering PGx testing.Results: Our review of the literature shows a lack of consensus about the need for and type of informed consent for PGx testing. We identified 35 companies offering PGx testing and were able to confirm consent practices for 22 of those. We found a range of variability in the consent practices regarding the consent approach and information disclosed.Conclusion: Variability in the consent practices among laboratories offering PGx testing mirrors the ambiguous practices and recommendations reported in the literature. Establishing a minimal set of information to be disclosed to patients may help address the disparities in consent practice.